Understory growth of Paris polyphylla accumulates a reservoir of secondary metabolites of plants - Yan, Xinru; Wang, Dong; Zhang, Ao; Xia, Jing; Jiao, Jinlong; Ghanim, Murad; Xiaokun, Ou; He, Xiahong; Shi, Rui (Frontiers in Microbiology, 2024)
Paris polyphylla is an important traditional medicinal plant of the Himalayan region. It is extensively used for the production of natural steroidal saponins and flavonoids. Although, seed dormancy of wild plant can be broken to artificially maintain and regenerate through micropropagation in the laboratory, however, success of secondary metabolites production in higher quantity and synthesis of superior plant metabolites have been very limited. In this study, we present differential metabolic profiling of Paris polyphylla plants maintained for eight years in natural as well as greenhouse conditions.Untargeted profiling of metabolites through ultra-performance liquid chromatography/mass spectrometry, followed by statistical analysis, identified secondary metabolites that were enriched in naturally occurring plant roots, compared with greenhouse plant roots. Multivariate statistical analysis revealed the differential distribution of compounds between the two groups. Overall, we identified 1182 secondary metabolites, where 116 metabolites were differentially up regulated whereas 256 metabolites were down regulated. Whereas, 810 metabolites insignificantly varied in both the growing conditions. Kyoto Encyclopedia of Genes and Genomes analysis revealed that naturally forest grown Paris plants were significantly enriched in steroidal saponin, lipids, vitamins, flavonoids and flavonols. Analysis of top-10 differentially up-regulated secondary metabolites indicated significantly enriched quantity of spirost-5-en-3,12-diol and Kaempferol synthesis pathways, which are considered as free radical scavengers inside the cell. Additionally, veratramine alkaloids were also enriched in natural conditions. Our findings indicate that the naturally maintained Paris plants are suitable for extraction of medicinally important compounds. Our study establishes the causal relationship between the metabolic composition of the roots and their natural growth condition. This study highlights the importance of environmental conditions in biosynthesis of plant secondary metabolites.